Milk consumption in relation to incidence of nasopharyngeal carcinoma in 48 countries/regions. Issue 1 (December 2015) - Mai, Zhi-Ming; Lo, Ching-Man; Xu, Jun; Chan, King-Pan; Wong, Chit-Ming; Lung, Maria; Lam, Tai-Hing
Abstract Background Decreasing trends of nasopharyngeal carcinoma (NPC) incidence have been consistently reported in endemic populations but the etiology of NPC remains unclear. The objective of our study was to assess the international and local (Hong Kong) correlations of milk and dairy products per capita consumption with NPC incidence. Methods We conducted an ecological study in 48 countries/regions. Age standardized incidence rates of NPC were obtained from the Cancer Incidence in Five Continents. Dairy product consumption and Human Development Index were obtained from the Food and Agriculture Organization of the United Nations and the United Nations Development Programme. Spearman correlation, multivariate analysis and time-lagged analysis were performed. Results The negative correlations between milk consumption and decreased age standardized incidence rates of NPC were observed in the 48 countries/regions adjusting for Human Development Index in endemic countries/regions. In Hong Kong, multivariate analysis, after adjusting for other potential confounders, including salted fish, cigarette, vegetable consumption and socioeconomic status, showed consistently negative and significant correlations between milk consumption and NPC incidence (The strongest coefficient (β) was observed at 10-year lag in males [β = −0.439;P < 0.01] and in females [β = −0.258;P < 0.01]). Conclusions Our study showed the correlations on milk consumption per capita and against lower risk of NPC in 48 countries/regions and in Hong Kong. These hypothesis-generating results could support further studies on individual exposures and the disease.